On Postsecular Paradigm and Influence of Religion in the Field of New Medical Biotechnologies – Some Introductory Remarks - Ivanović, Zorica (Etnoantropolos̆ki problemi, 2018)
Over the last couple of decades the phenomenon denoted as “return of religion” has become the subject of discussion in the social disciplines and humanities. Various authors stress that the social relevance of religion is becoming more obvious in the public and political spheres of the contemporary secular societies, as well as in the international relations and world politics. According to some interpretations, these phenomena allow thinking and talking about the contemporarity as a “postsecular age”. The paper discusses the basic assumptions of the postsecular paradigm and points to the limitations of the very concept of “postsecularity”. At the same time, the aim of the paper is to point to the importance of the relationship between religion and policy in the field of the new medical biotechnologies as one, but not exclusive aspect of anthropological research of the religious responses to the new possibilities raised by the biotechnological innovations.